FINANCIAL PERFORMANCE ANALYSIS OF FOOD SMES: A CASE STUDY IN SUKOHARJO REGENCY - Sundari, Mei Tri; Rahayu, Endang Siti; Irianto, Heru; Handayani, Sugiharti Mulya; Setyowati, Setyowati (Universitas Sebelas Maret, 2023)
This research aims to determine the costs, receipts, business advantages, and business feasibility of food Small Medium Enterprise (SMEs). The primary method used in this study is analytical descriptive with survey techniques. This research involved food SMEs entrepreneurs in Sukoharjo Regency with several 50 respondents. The sampling method uses a simple random sampling method. Data is obtained by interview and observation methods. The analytical techniques used are profit analysis, R/C ratio, liquidity analysis, solvency, business rentability, and risk analysis. The results showed that the RoA value was 12.102% so that the Food SMEs in Sukoharjo Regency showed possible outcomes to be developed. SMEs' solvency value represents a figure of 0.016%, based on creditors funding the business of 0.016% of the total assets held.